The Existence of Silariang Customary Delik In The Customary Law of Kajang Kab. Bulukumba Against Indonesian Law - Andalusia, Zahra Zhafira; Kansil, Christine ST (Journal Research of Social Science, Economics, and Management, 2023)
The factors that cause the occurrence of Silariang based on the customary law of the Kajang tribe are social stratification factors, where there are degrees of class. The factor of the lack of education and the occurrence of complex thoughts following the times so that sometimes they tend to forget their own culture without any interference from parents or from the family. Economic factors sareals overy influential for the two people to live independently so that what they do is considered not to violate applicable customs. And the promiscuity factor is then the lack of parental attention. Then the legal consequences for Silariang perpetrators, according to the people of Batunilamung Village, are the forms of sanctions that apply in Batunilamung Village, which are divided into three parts, namely: First, Principal Babbala means the most severe sanctions, fines for palaku as much as Sampulonrua reala or in Indonesian currency equivalent to one million two hundred thousand rupiahs is converted into Sibilangan angruangpulo reala in Indonesian currency equivalent to eighty million rupiahs. Second, Tangnga Babbala means that a medium or medium sanction is fined as much as Karua real equivalent to eight hundred thousand rupiahs which is changed to Karua pulo reala (eight million rupiahs) and approximately sixty million rupiahs for now. Third, Cappa Babbala means the lightest sanction is Annan reala equivalent to six hundred thousand rupiah in Indonesian currency converted to Annanpulo reala (six million rupiah) and equivalent to forty million rupiahs if it is equal to the current currency value plus one roll of cloth. White. So to give sanctions to perpetrators of customary violators depending on the violation.